EFFECT OF CHEMICAL AND PHYSICAL VARIABLES IN THE PHOTO-ELECTROCHEMICAL REMOVAL OF ESTRIOL (E3) AND 17 α-ETHINYLESTRADIOL (EE2) IN AQUEOUS SOLUTION - Díaz, Naysa; Pérez-Rivera, Mónica; Castillo, Rosario; Mundaca, Rodolfo; Aravena, Felipe; Aranda, Mario; Peña-Farfal, Carlos (Journal of the Chilean Chemical Society, 2019)
The effect of different variables in the electrochemical removal of estriol (E3) in aqueous solution was studied and it was compared with the removal of 17 α- Ethinylestradiol. The photoelectroxidations were carried out with DSA electrode (Ti/RuO2), varying the pH, substrate concentration and supporting electrolyte, potential configuration of saline bridge, reactor volume, and light source. Results for both Estriol and 17 α- Ethinylestradiol are similar, showing to be the best removals at concentrations of 500 ug/L of substrate, volumes to be treated of 90 ml of solution, saline bridge of 30 cm in length, voltages between 0.8 and 3, concentration of Na2SO4 of 0.1 M, pH between 6 and10, and UV lamp of 125 W.